A survey of the type of inter-religious dialogue model in Malaysia - Wan Yusuf, Wan Sabri (s.n, 2013)
This might be due to lack of information and understanding with regard to the methodology of dialogue and also about different types that it may take. Thus, the study is aimed at exploring few types of inter-religious dialogue that have been practiced by some organization that actively involved in dialogue such as Center for Civilizational Dialogue (CCD) and examining the designs for each types